ATOMISTIC DOCTRINE AND NUCLEAR-PERIPHERY IN LANGUAGE - Normuminov Sherzod Tuychievich (Academia Science Repository, 2023)
This article provides a concept of atomistic doctrine and its essence, as well as the presence of central (core) and lower (periphery), peripheral parts (areas) in language units and levels of linguistics, substantiates information about the role of atomistic doctrine in the field of linguistics.